2015
DOI: 10.1016/j.biopsych.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Bias in the Prefrontal Cortex of Psychopaths

Abstract: Our results suggest that a weakened link between emotional and cognitive domains in the psychopathic brain may combine with enhanced functional connections within frontal executive areas. The identified functional alterations are discussed in the context of potential contributors to the inflexible behavior displayed by individuals with psychopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
93
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 65 publications
9
93
2
1
Order By: Relevance
“…Although this functional connectivity result is novel, a number of previous studies have linked psychopathy with dACC dysfunction (Kiehl et al, 2001;Müller et al, 2003;Birbaumer et al, 2005;Koenigs, 2012;Ly et al, 2012;Meffert et al, 2013;ContrerasRodríguez et al, 2014;Cope et al, 2014). For example, task-based fMRI studies have associated psychopathy with decreased dACC activity across a variety of affective paradigms (Kiehl et al, 2001;Müller et al, 2003;Birbaumer et al, 2005;Meffert et al, 2013;Cope et al, 2014). Furthermore, two resting-state fMRI studies have reported diminished dACC-insula connectivity in psychopathy (Ly et al, 2012;Contreras-Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Although this functional connectivity result is novel, a number of previous studies have linked psychopathy with dACC dysfunction (Kiehl et al, 2001;Müller et al, 2003;Birbaumer et al, 2005;Koenigs, 2012;Ly et al, 2012;Meffert et al, 2013;ContrerasRodríguez et al, 2014;Cope et al, 2014). For example, task-based fMRI studies have associated psychopathy with decreased dACC activity across a variety of affective paradigms (Kiehl et al, 2001;Müller et al, 2003;Birbaumer et al, 2005;Meffert et al, 2013;Cope et al, 2014). Furthermore, two resting-state fMRI studies have reported diminished dACC-insula connectivity in psychopathy (Ly et al, 2012;Contreras-Rodríguez et al, 2014).…”
Section: Discussionmentioning
confidence: 70%
“…For example, task-based fMRI studies have associated psychopathy with decreased dACC activity across a variety of affective paradigms (Kiehl et al, 2001;Müller et al, 2003;Birbaumer et al, 2005;Meffert et al, 2013;Cope et al, 2014). Furthermore, two resting-state fMRI studies have reported diminished dACC-insula connectivity in psychopathy (Ly et al, 2012;Contreras-Rodríguez et al, 2014). Although the functional significance of decreased parietal-dACC connectivity in psychopathy is unknown, some theories suggest the interaction between these regions, as portions of the FPN and CON or as part of the unitary frontoparietal control system, could be important for integrating salient emotional and cognitive information to facilitate goal-directed action (Vincent et al, 2008; Menon, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within these theories, the amygdala is generally hyporesponsive to negative affective stimuli and lacks optimal functional interactions with paralimbic neurocircuits, leading to deficient affective reactivity (particularly to fear), biased attention modulation, and poor associative learning [Anderson and Kiehl, 2012; Blair, 2013a; Blair, 2015]. Very few studies, though, have actually investigated amygdala functional networks in relation to psychopathy, yielding conflicting results of both enhanced and diminished network integrity [Aghajani et al, 2016; Contreras‐Rodriguez et al, 2015; Decety et al, 2013a; Finger et al, 2012; Marsh et al, 2011; Motzkin et al, 2011; Yoder et al, 2015]. Most of these studies additionally examined psychopathy as a categorical or unidimensional construct, overlooking its behaviorally and neuronally separable trait assemblies [Carre et al, 2013; Cohn et al, 2014, 2015; Philippi et al, 2015; Sadeh and Verona, 2008; Seara‐Cardoso and Viding, 2014].…”
Section: Introductionmentioning
confidence: 99%